Comparison of edible grade whey, granular whey, and dairylac 80 as lactose sources for nursery pig diets - J C Woodworth; B W James; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
Two hundred ten weanling pigs (initially 12.4 lb and 18 ± 2 d of age) were used in a 14-d growth assay to determine the influence of various lactose sources and levels on nursery pig performance. From d 0 to 14, the mean ADG and ADFI of pigs fed additional lactose, regardless of source, was greater and tended to be greater compared to those fed no supplemental lactose. Pigs fed edible grade whey had increased ADFI and tended to have increased ADG as lactose increased from 9 to 18%. When Dairylac 80ï›š or granular whey was included in the diet, ADG and ADFI were increased over the control, but no further improvement above the 9% level was observed. However, pigs fed 9% granular whey and Dairylac 80 had similar performance to those fed 18% edible grade whey. For pigs fed Dairylac 80, F/G also improved linearly as lactose increased to 18% in the diet. No differences in growth performance were observed among lactose sources used in this study.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Pig; Lactose; Whey